SYSTEM OF PREPARATION OF FUTURE ECONOMISTS FOR ENTREPRENEURSHIP ACTIVITY - Elena Polishchuk (Scientific Journal of Pedagogy and Economics, 2019)
The article addresses the problem of preparing future economists for entrepreneurial activity. The purpose of the article is to substantiate the structure of the system of preparing future economists for entrepreneurial activity through its reflection - the model of the same name. Used methods: observation, questioning, interviews, testing of students, analysis of literature on the problem of research, curricula and programs. It has been substantiated that business activity is an independent activity carried out at its own risk, aimed at systematically receiving profits from the provision of various services, the sale of goods, etc. It is revealed that entrepreneurial activity is problematic for the majority of future economists, although many of them strive to start their own business after graduation. It has been established that students of the economics department are familiar with the state policy on creating favorable conditions for the development of small and medium-sized businesses, have a grasp of its state, including the most promising direction of business development in a particular region, etc. However, they are poorly informed about legal acts that underlie the organization of entrepreneurial activities have a general understanding of the technology of drawing up a business plan, the procedure for its approval to the appropriate authorities, their personal potential etc. It is proved that the activities of the institution of higher education for the preparation of future specialists in the economic sphere and management for this type of work is a holistic educational system that includes interrelated elements that have their own structure: goals and objectives, patterns and principles, organizational forms, methods and means functioning in the system of higher professional education and provide high quality training of future economists to professional activity in general, to entrepreneurial activities, in particular. The prospect of further research is seen in the experimental verification of the system of preparing future economists for entrepreneurial activity through approbation of its reflection - the model of the same name.